抗SIRPα抗体和双特异性巨噬细胞增强型抗体 (2021)
提供抗SIRPα抗体，包括多特异性抗SIRPα抗体，以及相关的组合物和方法。本发明的抗体结合至SIRPα，并能够阻断某一细胞上的CD47与吞噬细胞上的SIRPα的相互作用。对于SIRPα和第二抗原具有双特异性的抗体被称作双特异性巨噬细胞增强型(BiME)抗体，并且具有新兴的特性。主题抗SIRPα抗体可用于多种治疗方法。本发明的实施方式包括分离的抗体及其衍生物和片段，包含一种或多种所述抗SIRPα抗体的药物制剂；和产生所述抗体的细胞系。还提供了示例性抗SIRPα抗体的氨基酸序列。 Anti-SIRPα antibodies, including multi-specific anti-SIRPα antibodies, are provided, as are related compositions and methods. The antibodies of the disclosure bind to SIRPα and can block the interaction of CD47 on one cell with SIRPα on a phagocytic cell. Antibodies that are bispecific for SIRPα and a second antigen are termed Bi-specific Macrophage Enhancing (BiME) antibodies and have emergent properties. The subject anti-SIRPα antibodies find use in various therapeutic methods. Embodiments of the disclosure include isolated antibodies and derivatives and fragments thereof, pharmaceutical formulations comprising one or more of the anti-SIRPα antibodies; and cell lines that produce the antibodies. Also provided are amino acid sequences of exemplary anti-SIRPα antibodies.